Enriched artificial bee colony metaheuristic for hierarchical goal programming engineering design problems. (2016) - Dhouib, Saima; Dhouib, Souhail; Chabchoub, Habib
In this paper, a standard artificial bee colony (ABC) metaheuristic was enriched to optimise hierarchical goal programming (GP) engineering design problems. The proposed method was first adapted to support the GP by means of minimising deviations from fixed goals, and then enriched by the great deluge metaheuristic, especially in the onlooker bee phase, in order to increase its local search ability. The proposed metaheuristic is called great deluge artificial bee colony (GD-ABC). Experiments on four engineering design problems showed that the proposed GD-ABC metaheuristic converges rapidly and efficiently to solve those problems. The nonparametric Mann-Whitney U test was used to prove the comparison.